Identifying essential critical infrastructure workers during the COVID‐19 pandemic using standardized industry codes. Issue 7 (9th May 2022) - Billock, Rachael M.; Haring Sweeney, Marie; Steege, Andrea L.; Michaels, Ryan; Luckhaupt, Sara E.
Abstract: Background: The Cybersecurity and Infrastructure Security Agency (CISA) produced an advisory list identifying essential critical infrastructure workers (ECIW) during the coronavirus disease 2019 (COVID‐19) response. The CISA advisory list is the most common national definition of ECIW but has not been mapped to United States (U.S.) Census industry codes (CICs) to readily identify these worker populations in public health data sources. Methods: We identified essential critical infrastructure industry designations corresponding to v4.0 of the CISA advisory list for all six‐digit North American Industry Classification System (NAICS) codes and cross‐walked NAICS codes to CICs. CICs were grouped as essential, non‐essential, or mixed essential/non‐essential according to component NAICS industries. We also obtained national estimated population sizes for NAICS and Census industries and cross‐tabulated Census industry and occupation codes to identify industry‐occupation pairs. Results: We produced and made publicly available spreadsheets containing essential industry designations corresponding to v4.0 of the CISA advisory list for NAICS and Census industry titles and codes and population estimates by six‐digit NAICS industry, Census industry, and Census industry‐occupation pair. The CISA advisory list is highly inclusive and contains most industries and U.S. workers; 71.0% of Census industries comprising 80.6% of workers and 80.7% of NAICS industries comprising 87.1% of workers were designated as essential. Conclusions: We identified workers in essential critical infrastructure industries as defined by CISA using standardized industry codes. These classifications may support public health interventions and analyses related to the COVID‐19 pandemic and future public health crises.